When Algerian Arabic and Standard Arabic are used in the French Algerian comic book.: Case of SLIM’s BAD NEWS - DJEGHAR , Achraf (Journal of Human Sciences, 2022)
The Algerian comic strip has known several stages and milestones from colonization to the present day. What is remarkable in these drawings is the humorous quality that can be seen through the graphics, the illustrations, the characters that reflect the social reality and the cultural and language specificities. In these drawings, several linguistic codes have caught our attention, the cartoonists resort to the play of words, to different registers of languages, use a language to arouse the reader’s imagination through humour. All these specificities testify to the richness of this field in terms of language contact. It is precisely the very essence of our contribution that aims to study the presence of languages other than French in Slim’s comic strip ‘BAD NEWS’ published in the Algerian French-language daily ‘Le soir d’Algérie’. We will analyze the use of borrowing from the standard Arabic and Algerian language and understand its usefulness.